Europe in Search of New Foreign Policy Strategies: German, French and British Think Tanks’ Approaches - Pavel P. Timofeev; Elena M. Kharitonova; Maria V. Khorolskaya (Современная Европа)
The article focuses on the positions and assessments of the current international political situation presented in the think tanks’ policy papers in three European states: the United Kingdom, France and Germany. The relevance of the article stems from the new geopolitical reality, that puts pressure not only on national governments, but also on the analytical and expert community and urges them to reassess their views on their countries’ foreign policy, come up with new ideas and put forward updated visions of strategic priorities. The authors apply comparative analysis. The article uses specially selected key policy documents of the centers as well as the speeches and articles by the leaders of the think tanks published in 2022 and 2023. It examines and compares expert positions regarding the continued support to Ukraine, interaction with Russia, their views on the EU role in the changing global environment, relationships with the US, China and the Global South. The article identifies common themes and discrepancies between the positions, as well as key ideas and envisioned scenarios of the future developments. Basing on the analysed materials, the authors come to a conclusion that while political leaders make statements about European unity, the publications of the think tanks reveal substantial discrepancies on many concrete issues. European experts share common vision regarding the assessment of the ongoing shifts, agree that the world today is undergoing transformation and fragmentation, highlighting the Ukrainian crisis as a watershed event in the EU foreign policy development. However, British, German and French think tanks have different views on the ways forward in response to the emerging challenges.